(untitled) (Bangladesh Journal of Zoology, 2017)
DNA barcoding has been proposed as a means of quick species identification using a short standardized segment of DNA. Two species (Eleotris fusca and Glossogobius giuris) from the family Gobiidae and Eleotridae were selected for DNA barcoding using samples collected from different regions of Bangladesh. Cytochrome Oxidase Subunit I (COI) gene was sequenced from two different gobi fishes and compared with two previously published similar sequences from the genera Eleotris and Glossogobius. Multiple sequence alignment and the molecular systematic study were performed. The DNA barcode technique identified the two species. The study provides a good example of how DNA barcoding can build upon its primary mission of species identification and use available data to integrate genetic variation investigated at the local scale into a global framework. Bangladesh J. Zool. 44(2): 175-184, 2016